Potential Energy Surface of NO on Pt(997): Adsorbed States and Surface Diffusion. (26th October 2011) - Tsukahara, N.; Yoshinobu, J.
Abstract : The potential energy surface (PES) of NO on Pt(997) has been elucidated: the adsorption states and diffusion processes of NO on Pt(997) at low coverage were investigated by using infrared reflection absorption spectroscopy (IRAS) and scanning tunneling microscopy (STM). When NO molecules adsorb on a surface at a low temperature (11 K), each molecule transiently migrates on the surface from the first impact point to a possible adsorption site. We found that there are four stable adsorption sites for NO on Pt(997): a bridge site of the upper step, an fcc- (or hcp-) hollow site of the terrace, an on-top site of the terrace, and an fcc-hollow site of the lower step. At higher temperatures above 45 K, NO molecules start to migrate thermally to more stable adsorption sites on a terrace, and they are finally trapped at the bridge sites of the step, which are the most stable among the four sites.